A new regional classification for mobile telecommunications diffusion policy in China: Using the innovation and imitation coefficients - Jinyang Lima; Changi Nama; Seongcheol Kimb (International Telecommunications Society (ITS), 2012)
While Chinese telecommunications industry has been continuously developing, the penetration rate of mobile telecommunications by province in China is distributed from less than 40% to larger than 100% in 2009. This regional disparity in terms of mobile telecommunications penetration rate is due to various socioeconomic factors such as income level, occupation structure, education level. The purpose of this paper is to suggest a new approach for regional classification based on the diffusion characteristics of each province for more effective and efficient mobile telecommunication's diffusion policy and strategy. First, this paper estimates diffusion parameters, including an innovation coefficient and imitation coefficient of 31 provinces using mobile subscription data, and then classifies the provinces into six groups using cluster analysis based on the estimated innovation coefficient and imitation coefficients. The clusters are also significantly different in terms of socioeconomic perspective such as income level. The results of cluster analysis imply that the traditional regional classifications are too simple and should be divided more in detail in terms of innovation and imitation coefficients in the case of developing mobile telecommunications strategies. This new regional classification (six clusters) can be used for not only 3G diffusion policy but also the future mobile telecommunications technology diffusion policy. In China, 3G service was started in January 2009 as Chinese government awarded 3G cellular licenses. Finally, the managerial and political implications are addressed based on the new regional classification.
Keywords: 330; Regional classification; Innovation coefficient; Imitation coefficient; Cluster analysis; Mobile telecommunications; China